1147. Short Course of Voriconazole Therapy as a Risk Factor for Relapse of Invasive Pulmonary Aspergillosis. (31st December 2020) - Shin, Dong Hoon; Yoo, Seung-Jin; Jung, Jongtak; Jun, Kang Il; Kim, Hyungjin; Kang, Chang Kyung; Song, Kyung Ho; Choe, Pyoeng Gyun; Park, Wan Beom; Bang, Ji-Hwan; Kim, Eu Suk; Park, Sang Won; et al.
Abstract: Background: Invasive pulmonary aspergillosis (IPA) is a life-threatening opportunistic infection which usually occurs in immunocompromised patients. Recommended duration of voriconazole therapy is a minimum of 6-12 weeks for IPA, despite the lack of any firm evidence. In addition, risk factors for relapse of IPA are still unclear. Here, we explored risk factors for IPA relapse after initial treatment. Methods: All patients with proven or probable IPA who had finished voriconazole treatment between 2005 and 2019 in a tertiary-care hospital were reviewed. IPA relapse was defined as re-diagnosis of proven or probable IPA at the same site within 1 year after treatment termination. Short course of voriconazole treatment was defined as a treatment less than 9 weeks, which is a median of the recommended minimum duration of therapy from the Infectious Disease Society of America. The radiological response was defined as a reduction in IPA burden by more than 50% on chest computed tomography (CT). Results: Of 87 patients who had completed voriconazole treatment, 14 (16.1%) experienced IPA relapse. Multivariable Cox regression identified that short voriconazole treatment duration (adjusted hazard ratio [aHR], 3.7; 95% confidence interval [CI], 1.1–12.3; P=0.033) and radiological non-response (aHR, 4.6; 95% CI, 1.2–17.5; P=0.026) were independently associated with relapse of IPA after adjusting for several clinical risk factors. Conclusion: Less improvement in CT, and short duration of voriconazole therapy were the independent risk factors for relapse after treatment of IPA. Longer duration of therapy should be considered for those at higher risk of relapse. Disclosures: All Authors : No reported disclosures